Assessment for No Mobile Phone Phobia (Nomophobia) - Hadi , Burhan; Hussein , Ali Faris Abdul; Al Asadi , Kafi Mohammad Nasir (International Journal of Psychosocial Rehabilitation, 2020)
Background: Background: mobile phones today have grown to be an important section of our techno-culture mostly on more youthful human population. Discomfort, anxiety, nervousness, or distress caused by moving away from the cell phone is called "Nomophobia". Objective: this study was conducted to identify and assess the nomophobia and some variables that have a relationship and influence the subject of the study.Methodology: assessed for nomophobia through a special questionnaire to measure. The questionnaire consisted of (20) question. Each question consists of seven levels of answer according to the Likert scale. The ratings of each element were classified and the grades were classified into "mild "21-59", "moderate" "66-99", and "severe "more than 100" degrees. A study was conducted on random sample of one hundred individuals from different age groups. A tool was used to measure nomophobia in the participating sample. The information analyzed by applying descriptive statistical measures in addition to inferential statistical measures.Results: The results showed that the highest participation rate was 52% in males for the sex, whereas urban area was 54% and 53% were unemployed. The percentage of young people was the highest by 81% and the percentage of unmarried was the highest by 64%, as well as the proportion of recipients of university degree is the highest by 70% This confirms that the proportion of unemployed graduates are the highest in the sample as well as the age group (15-30) is highest share of research. The severe nomophobia is 70% and the lowest percentage is mild nomophobia by 9% and the moderate nomophobia rate is 21%.Conclusion: mobile phones and new technology formed our daily life, several aspects, the most important negative and positive.Recommendations: The study recommended practical tips to reduce the disadvantages of relying on mobile phone, which is to spend time with family at the end of the week without using technology and not take the phone to the bedroom because it is harmful to human health and do not use the phone in the indoor, such as car or elevator and Do not talk in the mobile phone while charging and keep the phone away from you while you sleep, eat, sit with family members, do not use some social applications everyday unless necessary, receive urgent messages and set up centers and sanatoriums to reduce addiction and phobia in children and young people.